ANALYSIS OF THE IMPLEMENTATION OF SELECTIVE POLICY IN STRENGTHENING OF BORDER CONTROLS AT IMMIGRATION CHECKPOINT - Kadek Fransisca Siba; Anindito R. Wiraputra (Polteknik Imigrasi, 2021)
The problem of illegal immigrants has threatened the security and sovereignty of the Indonesian state. Even in 2013, the trend of illegal immigrants entering Indonesia increased by 12%. Most of them come from conflict-affected countries. Therefore, to prevent the increasing number of illegal immigrants from entering Indonesian territory, Indonesian immigration needs to strengthen border controls at the immigration checkpoints by continuing to implement immigration policy, namely selective policy. This policy only allows foreigners who provide benefits and does not endanger security and public order to be allowed to enter and reside in Indonesian territory. This policy supports the implementation of the immigration function, namely law enforcement and state security, particularly in preventing illegal immigrants who intend to enter Indonesian territory. The research method used is qualitative normative legal research with data analysis sourced from books, writings, scientific papers, and laws and regulations that are related to research.